(untitled) (Research, Society and Development, 2023)
Health is a state of balance between an individual’s physical, social and mental well-being. Although all parameters have the same importance in preserving homeostasis, mental health does not receive due attention. Since the beginning of history, societies have questioned mental health, through the observation of those who had atypical behaviors. However, over the years, much has evolved in the way of looking at mental disorders, as well as in the way of dealing and treating according to the needs of each one, through science. Psychological disorders are characterized by promoting changes in an individual’s behavior and reasoning. These disorders, in some cases, require pharmacological treatment in addition to therapy, which is carried out through psychotropic drugs, these drugs are capable of modifying or stimulating an improvement in mood, however, in addition to the beneficial effects, they can also cause dependence and some unwanted reactions. that makes adherence to treatment difficult. In this context, the present study aimed to carry out a bibliographical survey on the importance of the pharmacist’s role in mental health care. For the accomplishment, articles present in electronic databases were used. The selection was made based on a careful interpretation of these articles. After data collection, the information was compiled and later described in order to provide innovative conclusions on the subject.